PEMBUATAN TAMAN BELAJAR KI HAJAR DEWANTARA (PTBK) DI DUKUH KARANG PASEBAN BAYAT - Nanag Yuniantoro; Dwi Isnanto; Ardiyanti Fitriadewi; Andina Winjani (Pelita - Jurnal Penelitian Mahasiswa UNY, 2014)
AbstractAt Karang, Paseban, Bayat from 2008 to 2013 there were 1 to 2 elementaryschool children who did not pass to the next grade of their elementary education. Oneof the reasons is their low reading interest. They would rather play games than read.The long term goal of this program is to improve the quality of education and learningcommunity to develop creativity, whereas the short term one is to create a kind oflearning park named Ki Hajar Dewantara and organize activities that are beneficial tothe society. The method of the program consists of preparing the permit, equipmentand materials, and socializing the program to the community, and implementing,monitoring, evaluating, and completing the program. The results of the program are alearning park named Ki Hajar Dewantara at Karang, Paseban, Bayat, establishing aboard comprising of the young people at Karang to take care of the park, and a changein the mindset of the children and youth in spending the leisure time, which is provedby the increasing number of visits to the park during the six-week study, from 12children at the end of June to 59 children per week in the beginning of August. Theexistence of the park brings the benefit of the culture of reading in the society.